'… might go to Birmingham, Leeds … up round there, Manchester … and then we always come back here …': The conceptualisation of place among a group of Irish women travellers. (March 2014) - Piazza, Roberta
This study of a group of Irish women travellers in the South of England provides the opportunity for a discourse of situated self-identity within a mobilities paradigm. The stability-aspiring travellers' community, to which the women in the study belong, invites a reflection on existing approaches to place-identity in that these women conceptualise their place in terms of its positive affordances and services that make their life liveable. The five women's emerging discourses of both mobility and stability suggest that their emotional attachment to the place where they momentarily reside can be explained in terms of the beneficial results they gain from it. A scrutiny of the deictics used by the women, as well as a qualitative interactional analysis of the semi-structured interviews, suggests that for these travellers the sociolinguistic phenomenon of place-identity is layered and scalar so as to account for a loyalty to their distant provenience from Ireland, together with their present attachment to the encampment. As these women conceptualise place in terms of what it can provide for their families and community, their often idealised conceptualisation of locality resembles a Foucauldian 'heterotopia of compensation', in which the meticulous functioning of the site protects the community and defends it from outer contaminations.